Studies on Crosslinking Efficiency of Carboxylated Polymers with Multifunctional Carbodiimides - Eryd Berlin,Evelina (2025)
Multifunctional carbodiimides (CDIs) present a safer, non-toxic alternative to conventional isocyanate crosslinkers in waterborne floor coatings. However, the inconsistent performance of CDI-crosslinked coatings has hindered the widespread adoption. This study investigates the key factors governing crosslinking efficiency to improve reliability of CDI-based systems. It was determined that crosslinker type is the most critical factor, with one CDI (R-71) forming rigid, chemically resistant networks, while another (HYD) acted primarily as a plasticizer. Increasing the carboxylic acid content in the polymer backbone enhanced crosslink density, leading to higher stiffness and chemical resistance. However, this also promoted embrittlement and poor adhesion at high concentrations due to over-crosslinking. The choice of carboxylic acid was also significant. Methacrylic acid generally yielded more robust networks than acrylic acid, due to steric effects that favor stable crosslink formation. Neutralizing agents also had a significant influence on the final coating properties. Ammonia produced the hardest and most resistant coatings, as its small size and volatility facilitated the formation of a dense network. In contrast, bulkier amines plasticized the coating, and those with additional functional groups formed secondary interactions that interfered with covalent crosslinking. The central conclusion is that achieving a high-performance coating requires a balanced formulation. Excessive crosslink density sacrifices adhesion for chemical resistance, while more flexible networks show the opposite. Therefore, precise control over the polymer design must be matched with the selection of a suitable carbodiimide to consistently obtain coatings with the desired properties
Keywords: carbodiimides; multifunctional carbodiimides; crosslinking agent; crosslinking efficiency; floor coating; polyacrylate; neutralizing agent; polymer technology